2016
DOI: 10.18632/oncotarget.9574
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating L1CAM expression in human endometrial cancer using qRT-PCR

Abstract: BackgroundManagement of endometrial carcinoma (EC) still needs improvement of risk assessment. Recently, L1CAM immunohistochemical (IHC) evaluation showed a unique value to predict the outcome of early EC. However IHC results are often conflicting for lack of inter-laboratory standardisation.MethodsHere, as a proof of concept and to increase reproducibility we assayed eighty-two EC and 26 normal endometrium samples for L1CAM expression (L1CAMEXP) via qRT-PCR. The IHC evaluation was performed in 50 cancer sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…L1CAM functions mostly in proliferation, migration, invasion, and survival through L1CAM homophilic interaction or heterophilic interactions with other cell adhesion molecules, integrins, or growth factor receptor, while the cellular properties are not homogeneous among different types of cancers ( 12 ). Recently, it has been reported that L1CAM was involved in progression of endometrial cancer ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…L1CAM functions mostly in proliferation, migration, invasion, and survival through L1CAM homophilic interaction or heterophilic interactions with other cell adhesion molecules, integrins, or growth factor receptor, while the cellular properties are not homogeneous among different types of cancers ( 12 ). Recently, it has been reported that L1CAM was involved in progression of endometrial cancer ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thirty studies [ 5 8 , 12 , 14 , 15 , 17 25 , 27 , 28 , 30 37 , 39 41 , 43 ] with data from 7743 patients were available to evaluate the effect of L1CAM expression on OS. The random-effects model was applied to calculate the pooled HR and 95%CI because of the significant heterogeneity among studies (I 2 =81.8%, P<0.01).…”
Section: Resultsmentioning
confidence: 99%
“…THBS1 is an endogenous angiogenesis inhibitor which has previously been associated with the development of tumor microenvironment and angiogenesis and has been shown to promote migration of cancer cells (60 -62). L1CAM is a cell adhesion molecule, which was originally identified as a neural cell adhesion molecule in the central nervous system (63), but L1CAM expression has been identified in a variety of tumor types (64) and has been recently reported the be involved in the progression of endometrial cancer (65). Lastly, IGHG2 forms the constant region of immunoglobulin heavy chains.…”
Section: Discussionmentioning
confidence: 99%